A Guide to Effective Customer Service - Universal Training System Co. (Illinois Bank Administration Institute, 1987)
This book presents customer service techniques that are essential tools for achieving good customer relationships. Using the techniques described in the text will help you develop skills that will make your job easier and result in satisfied customers.
osc 6/6/17
Loans